2019
DOI: 10.1038/s41438-019-0167-x
|View full text |Cite
|
Sign up to set email alerts
|

Auxin response factor 6A regulates photosynthesis, sugar accumulation, and fruit development in tomato

Abstract: Auxin response factors (ARFs) are involved in auxin-mediated transcriptional regulation in plants. In this study, we performed functional characterization of SlARF6A in tomato. SlARF6A is located in the nucleus and exhibits transcriptional activator activity. Overexpression of SlARF6A increased chlorophyll contents in the fruits and leaves of tomato plants, whereas downregulation of SlARF6A decreased chlorophyll contents compared with those of wild-type (WT) plants. Analysis of chloroplasts using transmission … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
62
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(70 citation statements)
references
References 64 publications
(78 reference statements)
1
62
0
Order By: Relevance
“…CeARF_11, a homologue of Arabidopsis ARF16, was also co-expressed with several photosynthetic downstream genes and with one of the top-ranked genes in the GCN, CeARF_9. Auxin response regulators have been recently shown to play antagonistic roles in photosynthesis regulation in tomato, and the SlARF6A gene was shown to positively affects photosynthesis in fruits and leaves of tomato plants [63]. Our data are consistent with a major role of auxin response in coordinating photosynthesis and leaf development.…”
Section: Developmental Genes In Cluster Three Linked To Positive Regusupporting
confidence: 86%
“…CeARF_11, a homologue of Arabidopsis ARF16, was also co-expressed with several photosynthetic downstream genes and with one of the top-ranked genes in the GCN, CeARF_9. Auxin response regulators have been recently shown to play antagonistic roles in photosynthesis regulation in tomato, and the SlARF6A gene was shown to positively affects photosynthesis in fruits and leaves of tomato plants [63]. Our data are consistent with a major role of auxin response in coordinating photosynthesis and leaf development.…”
Section: Developmental Genes In Cluster Three Linked To Positive Regusupporting
confidence: 86%
“…The role of auxin in plant cell expansion is well established [20]. Many studies have demonstrated the role of auxin response factors (ARFs), the main regulators of auxin, in cell division and plant growth [21,23,24,62]. We identified eight auxin-related genes showing significant differential expression among the two cultivars.…”
Section: Discussionmentioning
confidence: 96%
“…An increase in auxin and cytokinin levels in seeds is correlated with fruit growth stages [19]. The role of auxin in cell expansion during fruit development stages is well established [20,21]. Numerous studies have demonstrated the role of auxin response factors (ARFs), the main regulators of auxin, in cell division and growth during fruit development [20][21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although both SlARF2A and SlARF2B contribute to tomato fruit ripening, the SlARF2A transcript is responsive to exogenous ethylene, auxin and ABA, suggesting that SlARF2A intercorrelates auxin, ethylene and ABA signalling during fruit ripening (Breitel et al, 2016). Moreover, SlARF4 negatively regulates chlorophyll accumulation and starch biosynthesis in tomato fruit, whereas SlARF10 and SlARF6A positively regulate chlorophyll content and sugar accumulation (Sagar et al, 2013;Yuan et al, 2018Yuan et al, , 2019. In addition, ABA is also involved in ethylene signalling, with exogenous ABA application inducing the ethylene biosynthesis genes (Zhang et al, 2009).…”
Section: Aba Plays a Pivotal Role In Nonclimacteric Fruit Ripeningmentioning
confidence: 99%